2021
DOI: 10.1016/j.ultsonch.2021.105846
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic synthesis of Mn-Ni-Fe tri-metallic oxide anchored on polymer-grafted conductive carbon for rechargeable zinc-air battery

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Despite these benefits, metal oxides still exhibit limitations concerning their capacity and cycling performance. First, certain metal oxides inherently have low conductivity . Second, the mechanical stress induced by volume changes during lithiation and delithiation cycling can affect the integrity of the metal oxide material, which can lead to particle rupture, loss of electrical contacts, and overall material degradation during repeated cycles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, metal oxides still exhibit limitations concerning their capacity and cycling performance. First, certain metal oxides inherently have low conductivity . Second, the mechanical stress induced by volume changes during lithiation and delithiation cycling can affect the integrity of the metal oxide material, which can lead to particle rupture, loss of electrical contacts, and overall material degradation during repeated cycles .…”
Section: Introductionmentioning
confidence: 99%
“…First, certain metal oxides inherently have low conductivity. 10 Second, the mechanical stress induced by volume changes during lithiation and delithiation cycling can affect the integrity of the metal oxide material, which can lead to particle rupture, loss of electrical contacts, and overall material degradation during repeated cycles. 11 demonstrated that conductive polymer networks can alleviate battery capacity decline by minimizing side reactions and reducing electrochemical reaction polarization.…”
Section: Introductionmentioning
confidence: 99%
“… 24 As demonstrated, the ultrasonic-assisted approach has been favorable for the formation of hybrid or nanomaterials without using any additional chemical reagents or apparatus. 25 To the best of our knowledge, a simple coupling ultrasonic-assisted impregnation and precipitation is a reasonable method to produce magnetic recyclable Fe 3 O 4 /biochar photocatalysts from rice husk for ciprofloxacin photodegradation in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al [10] used reactive free radicals produced by ultrasonic irradiation to produce Mn-Ni-Fe tri-metallic oxide. Generates hierarchical pores upon anchored such tri-metallic oxide on polymer grafted carbon black which contributes to enhanced electrocatalytic performance (oxygen reduction reaction (ORR)/oxygen evolution reaction (OER)) towards rechargeable zinc-air batteries.…”
mentioning
confidence: 99%